Desenvolvimento de modelos baseados em medidas hiperespectrais NIR para análise de sementes e caracterização de algodoeiros arbóreos. - Araújo, Fernando dos Santos (2019)
Cotton growing in Brazil is characterized by a great diversity of production systems, including modernization intense based in agribusiness from Cerrado region, beside small production centers directed to niche markets linked to family-based agriculture that is expansion process and structuring in the Semiarid Region. Thus, this study aimed to develop models based on NIR hyperspectral measurements for seed analysis and to characterize local forms of cotton in terms of diversity and genetic structure, technological quality of fiber and potential use of leaf biomass for forage purposes. Using the near infrared hyperspectral imaging technique associated with chemometric analysis it was possible to develop new methods capable of classifying immature and healthy cotton seeds and viable and non-viable seeds in a fast, safe and non destructive manner. The genetic marker of the PCR-based Inter Simple Sequence Repet used was able to reveal patterns of diversity and intraspecific genetic structuring of perennial cotton (Gossypium hirsutum L. marie-galante and Gossypium barbadense L.), and therefore, promising for genetic characterization. Genetic characterization the populations G. hirsutum L. r. marie-galante using this genetic-molecular marker indicated low levels of total and intrapopulation genetic diversity, high genetic differentiation, low gene flow and are structured into two spatially structured genetic groups. The cotton plume evaluation of the4 populations showed that most fiber technological characteristics are within the expected range for modern cultivars. Agronomic characteristics vary among these populations and are influenced by the developmental phenophase. Its leaf biomass presents a chemical-bromatological profile potentially suitable for ruminant feeding in all phenophases, but its quantity and chemical-bromatological quality are higher in flowering and post-fruiting phenophases.